SYIAR MELALUI SYAIR (EKSISTENSI KESENIAN TRADISIONAL SEBAGAI MEDIA DAKWAH DI ERA BUDAYA POPULER) - Nor Kholis (al-Balagh : Jurnal Dakwah dan Komunikasi, 2018)
Traditioanl art in the era of popular culture has begun to be abandoned. One form of traditional art can be used as a medium of propaganda. This research want to see hoe the existetence, fungtion and value of traditional art Kubro Siswo in the era of popular culture. The method used in this research is descriptive – analysis. The results show traditional art still in demand because it has its own fascination after transformation happened. The transformation is a result of planned chance from the internal aspect. While the function of the art that still can be used as syiar media and also as social relation bond. While the values there are accepted by the society toward those only limited on entertainment, not yet understood its philosopical values. However with those art, the society can be used as facility to strengththen and increase quality of the relationship one another.